Vascular Function in Patients After Myocardial Infarction: The Importance of Physical Activity - Tršan, Jure; Košuta, Daniel; Rajkovič﻿﻿﻿, Uroš; Fras, Zlatko; Jug, Borut; Novaković﻿﻿﻿, Marko (Frontiers in Physiology, 2021)
Background Patients after myocardial infarction have impaired vascular function. However, effects of lifestyle, e.g. physical activity level, on endothelial function and arterial stiffness remain scarce. The aim of our study was to investigate effects of physical activity level and risk factors on endothelial function and arterial stiffness. Methods In this cross-sectional study we ultrasonographically assessed parameters of vascular function, namely flow mediated dilation (FMD) of the brachial artery and carotid artery stiffness in patients after myocardial infarction referred to the cardiac rehabilitation. The International Physical Activity Questionnaire (IPAQ) was obtained from all participants. Based on the IPAQ, patients were classified into 3 groups: vigorous, moderate and low physical activity engagement. ANOVA was used for comparison among 3 groups using Bonferroni correction to determine differences between two sub-groups. Results One hundred and eight patients after myocardial infarction (mean age 53 ± 10 years) were included. There were significant differences in terms of FMD (8.2 vs. 4.2 vs. 1.9%, p<0.001) and pulse wave velocity (PWV), a measure of arterial stiffness (6.1 vs. 6.4 vs. 6.9 m/s, p=0.004) among groups of vigorous, moderate and low physical activity engagement, respectively. However, in younger patients only FMD remained associated with physical activity level, while arterial stiffness was not. Low physical activity engagement was a significant predictor of both FMD and PWV in univariate and multivariate models, adjusted for age, sex, and other risk factors. Conclusion Low physical activity level is associated with impaired endothelial function and increased arterial stiffness in patients after myocardial infarction. Future studies are warranted to address this issue in a context of cardiac rehabilitation protocols optimisation in order to improve vascular function in these patients.